A review on the factors influencing the attendance of postpartum diabetes screening for mothers with gestational diabetes mellitus - Thangarajah, Puganeswary; Minhat, Halimatus Sakdiah; Mohd Zulkefli, Nor Afiah; Ahmad, Norliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Women with gestational diabetes mellitus (GDM) during their pregnancy have a greater risk of developing overt diabetes mellitus and dysglycemia (prediabetes, impaired glucose tolerance or impaired fasting glucose) later in future, compared to mothers with normal pregnancy. Postpartum screening is crucial for early identification of type 2 diabetes (T2DM) in women with GDM. Nevertheless, despite various strategies, its rate remains low. A systematic review using databases of PubMed/Medline, Science Direct and CINAHL from 2008 to 2018, was conducted to identify the factors influencing the attendance of postpartum diabetes screening. Open access English articles, focusing on observational studies were reviewed. Primary screening of titles and abstracts of 91 articles were done, secondary screening of 31 articles resulted in 6 articles, included in this manuscript. Various factors identified to be associated with the attendance to postpartum diabetes screening, which are age, education, ethnicity, some obstetric factors like multiparty, and history of insulin usage previously. Many women fail to be screened for diabetes during the postpartum period, and this delays T2DM diagnosis, which in turn gives rise to various complications. Further research that considers these factors is necessary for developing interventions to improve postpartum T2DM screening for mothers with GDM during their pregnancy.